An analysis of citations to the fisheries research journal of the Philippines and Kalikasan, the Philippine journal of biology - Dizon, Leticia B. (1991)
An investigation was made of citations to two Philippine biological journals, the Fisheries Research Journal of the Philippines (FRJP) and Kalikasan, the Philippine Journal of Biology using citation analysis, a scientometric/bibliometric tool. The aim was to find out how scientists use these journals.